Eterminants of Employee Performance in Religion-Based NGO: Lessons From The Fundraising Division of The Dompet Dhuafa Amil Zakat Institution - Anwar Hadi Musaddad; Didin Hafidhuddin; Idqan Fahmi (Indonesian Journal of Business and Entrepreneurship (IJBE), 2019)
Working in a religion-based institution has some unique values compared to other institutions in general. These characteristics can be a distinguishing factor that influence employee performance between the two institutions that are interesting to be examined. This research focuses on analyzing the factors that influence the employee performance of Fundraising Division of the Dompet Dhuafa Amil Zakat Institution, e.g., the ability, effort, management support, internal division support, and program division support. The purposes of this research are 1) to analyze employee performance of the fundraising division; 2) to analyze factors that influence employee performance of the fundraising division and to compare the results with other institutions; and 3) to formulate the strategy to improve employee performance of the fundraising division. The data was collected using a structural questionnaire with the employee of the fundraising division as respondents. The data collected was then analyzed using descriptive analysis and Partial Least Square. The results indicate that the employee performance of the fundraising division was rated good. The effort factor, internal division support, and program division support have a significant positive effect on employee performance in the fundraising division. Leadership training, value internalization, and performance optimization are then selected as the strategies to increase employee performance of the fundraising division.Keywords: fundraising, employee performance, dompet dhuafa, PLS SEM